Demographic and clinical profiles of Plasmodium falciparum and Plasmodium vivax patients at a tertiary care centre in southwestern India. (December 2016) - Chery, Laura; Maki, Jennifer; Mascarenhas, Anjali; Walke, Jayashri; Gawas, Pooja; Almeida, Anvily; Fernandes, Mezia; Vaz, Marina; Ramanan, Rakesh; Shirodkar, Diksha; Bernabeu, Maria; Manoharan, Suresh; et al.
Abstract Background Malaria remains an important cause of morbidity and mortality in India. Though many comprehensive studies have been carried out in Africa and Southeast Asia to characterize and examine determinants ofPlasmodium falciparum andPlasmodium vivax malaria pathogenesis, fewer have been conducted in India. Methods A prospective study of malaria-positive individuals was conducted at Goa Medical College and Hospital (GMC) from 2012 to 2015 to identify demographic, diagnostic and clinical indicators associated withP. falciparum andP. vivax infection on univariate analysis. Results Between 2012 and 2015, 74, 571 febrile individuals, 6287 (8.4%) of whom were malaria positive, presented to GMC. The total number of malaria cases at GMC increased more than two-fold over four years, with bothP. vivax andP. falciparum cases present year-round. Some 1116 malaria-positive individuals (mean age = 27, 91% male), 88.2% of whom were born outside of Goa and 51% of whom were construction workers, were enroled in the study. Of 1088 confirmed malaria-positive patients, 77.0% hadP. vivax, 21.0% hadP. falciparum and 2.0% had mixed malaria. Patients over 40 years of age and withP. falciparum infection were significantly (p  < 0.001) more likely to be hospitalised than younger andP. vivax patients, respectively. While approximately equal percentages of hospitalisedP. falciparum (76.6%) andP. vivax (78.9%) cases presented with at least one WHO severity indicator, a greater percentage ofP. falciparum inpatients presented with at least two (43.9%, p  < 0.05) and at least three (29.9%, p  < 0.01) severity features. There were six deaths among the 182 hospitalised malaria positive patients, all of whom hadP. falciparum. Conclusion During the four year study period at GMC, the number of malaria cases increased substantially and the greatest burden of severe disease was contributed byP. falciparum .